FA Tool, herramienta de asignación de frecuencia en redes celulares por medio de algoritmos genéticos - Gómez Paredes, Juan Carlos; Acero Hernández, Jorge Andrés; García Suárez, Aldo Camilo (Ingeniería, 2003)
This paper presents a software, as solution to the problem of assignment of frequency in cellular nets,denominated FA Tool, able to carry out an estimate of the number of necessary channels for station bases and to determine a plan of frequencies by means of a process based on genetic algorithms (GA)modified, that it allows to establish the bases and a first approach to the study of the automatic optimization of frequencies.